Dynamic in situ control of heat rectification in graphene nano-ribbons using voltage-controlled strain - Shiri, Daryoush; Isacsson, Andreas (Frontiers in Nanotechnology, 2025)
An increasing number of papers propose routes to implement thermal counterparts of electronic rectification. These schemes are mainly based on combinations of crystal anharmonicity and broken mirror symmetry. With respect to graphene, proposals pivot around shape asymmetry induced by using hetero-structures of nano-patterned or defected sections of pristine graphene. Using Molecular Dynamics (MD) we show that it suffices to split a graphene nano-ribbon into two unequal strained sections using external force which leads to large asymmetry in the forward and reverse heat fluxes. We find that the corresponding rectification ratio is enhanced by up to 60%. Also, and more importantly, the polarity is controllable on-the-fly i.e., by changing the position where the force is applied. Based upon our results we propose a thermo-electric device which obviates the complex nano-patterning and lithography required to pattern graphene every time a new rectification value or sign is sought for, opening a route to simpler fabrication and characterization of phononic phenomena in 2D materials.